Tuberculosis: income inequality and interaction of the Family Health Strategy and the Bolsa Família Program - Marcela Paschoal Popolin; Maria Concebida da Cunha Garcia; Luiz Henrique Arroyo; Mellina Yamamura; Marcelino Santos Neto; Ludmila Barbosa Bandeira Rodrigues; Ana Angélica Rêgo de Queiroz; Inês Fronteira; Ricardo Alexandre Arcêncio (Universidade Federal de Goias, 2017)
This study aimed to verify tuberculosis (TB) incidence and mortality behavior in areas covered by the Family Health Strategy and Bolsa Família Program, with or with no income inequality. This is an ecological study of the 26 Brazilian federal states and the Federal District. We used univariate, multivariate and spatial analyzes. We calculated the univariate analysis, the measure of position (median) and the measure of dispersion (amplitude) of the variables. In the multivariate analysis, seven groups were identified through hierarchical grouping analysis. The thematic maps construction showed a heterogeneous distribution between the groups due to the specific characteristics. The study evidenced the epidemiological TB reality in Brazil and its behavior in areas covered by the Family Health Strategy and Bolsa Família Program. No differences were observed in incidence and mortality when coverage of these programs was satisfactory, which evidences the disease relation to other determinants.